Bioprospecting Indigenous Marine Microalgae for Polyunsaturated Fatty Acids Under Different Media Conditions - Jain, Priyanshu; Minhas, Amritpreet Kaur; Shukla, Sadhana; Puri, Munish; Barrow, Colin J.; Mandal, Shovon (Frontiers in Bioengineering and Biotechnology, 2022)
Graphical Abstract